2008
DOI: 10.1371/journal.pgen.1000214
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Mapping of Expression-QTLs Yields Insight into Human Gene Regulation

Abstract: Recent studies of the HapMap lymphoblastoid cell lines have identified large numbers of quantitative trait loci for gene expression (eQTLs). Reanalyzing these data using a novel Bayesian hierarchical model, we were able to create a surprisingly high-resolution map of the typical locations of sites that affect mRNA levels in cis. Strikingly, we found a strong enrichment of eQTLs in the 250 bp just upstream of the transcription end site (TES), in addition to an enrichment around the transcription start site (TSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
526
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 526 publications
(597 citation statements)
references
References 47 publications
67
526
4
Order By: Relevance
“…Both rs2298383 and rs3761422 are located in potential promoter regions upstream of several newly identified variants of ADORA2A exon 1 (Yu et al, 2004) near the corresponding transcription start sites. SNPs located within or immediately around these sites have been highlighted as having high potential to alter gene function (Veyrieras et al, 2008). In contrast to ADORA2A SNPs, no association of caffeineinduced anxiety was found with ADORA1 SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Both rs2298383 and rs3761422 are located in potential promoter regions upstream of several newly identified variants of ADORA2A exon 1 (Yu et al, 2004) near the corresponding transcription start sites. SNPs located within or immediately around these sites have been highlighted as having high potential to alter gene function (Veyrieras et al, 2008). In contrast to ADORA2A SNPs, no association of caffeineinduced anxiety was found with ADORA1 SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…80 RNA-Seq studies, and our recent work among them, 43 revealed that many genes annotated in currently available databases (ie, RefSeq, UCSC and Ensembl) have extended 3' UTRs, containing putative affecting donor and acceptor splice sites (GU and AG) altering the splicing of the coding exons. In detail, in (1) a canonically spliced pre-mRNA following the GU-AG rule; (2) an example of nucleotide variation/s occurring within the introns and generating a novel acceptor 'cryptic' splice site.…”
Section: Rna-seq In Human Complex Diseases V Costa Et Almentioning
confidence: 99%
“…To identify eQTL effects, eQTL databases were analyzed (Borel et al., 2011; Dimas et al., 2009; Dixon et al., 2007; Fehrmann et al., 2011; Greenawalt et al., 2011; Grundberg et al., 2009; GTEx Consortium, 2015; Kim, Cho, Lee, & Webster, 2012; Kirsten et al., 2015; Mehta et al., 2013; Myers et al., 2007; Ramasamy et al., 2014; Schadt et al., 2008; Schröder et al., 2011; Veyrieras et al., 2008; Westra et al., 2013; Xia et al., 2012; Zeller et al., 2010). We only considered SNPs identified in brain or blood tissue and eQTLs had to be replicated in at least one study.…”
Section: Methodsmentioning
confidence: 99%